Asymptomatic Malaria Correlates with Anaemia in Pregnant Women at Ouagadougou, Burkina Faso. (11th November 2012) - Douamba, Zoenabo; Bisseye, Cyrille; Djigma, Florencia W.; Compaoré, Tegwinde R.; Bazie, Valérie Jean Telesphore; Pietra, Virginio; Nikiema, Jean-Baptiste; Simpore, Jacques
Abstract : Sub-Saharan Africa records each year about thirty-two million pregnant women living in areas of high transmission of Plasmodium falciparum causing malaria. The aim of this study was to carve out the prevalence of asymptomatic malaria among pregnant women and to emphasize its influence on haematological markers. The prevalence of Plasmodium falciparum asymptomatic infection among pregnant women was 30% and 24% with rapid detection test (RDT) and microscopy, respectively. The prevalence of P. falciparum asymptomatic malaria was reduced among pregnant women using sulfadoxine-pyrimethamine's intermittent preventive treatment and 61% of them were anaemic. Anaemia was significantly more common in women infected with P. falciparum compared with the uninfected pregnant women. Most of the women had normal levels of homocysteine and low levels of folate, respectively. Therefore, the systematic diagnosis of malaria should be introduced to pregnant women as a part of the antenatal care.